Influence of diblock addition on tack in a polyacrylic triblock copolymer/tackifier system measured using a probe tack test. Issue 3 (22nd November 2012) - Yamamura, Kazuhiro; Fujii, Syuji; Nakamura, Yoshinobu; Fujiwara, Kazuko; Hikasa, Shigeki; Urahama, Yoshiaki
Abstract The influence of diblock copolymer addition on the tack properties of a polyacrylic triblock copolymer/tackifier system was investigated. For this purpose, poly(methyl methacrylate)‐block‐poly(n‐butyl acrylate)‐block‐poly(methyl methacrylate) triblock copolymer (MAM) and a 1/1 blend with a diblock copolymer consisting of the same components (MA) were used as base polymers, and a tackifier was added in amounts ranging from 10 to 30 wt %. The temperature dependence of tack was measured by a probe tack test. The tack of MAM/MA at room temperature was significantly higher than that of MAM, and the improvement of MAM/MA upon the addition of the tackifier was higher than that of MAM. The peeling process at the probe/adhesive interface during the probe tack test was observed using a high‐speed microscope. It was found that for MAM/MA, cavitation was caused in the entire adhesive layer, and peeling initiation was delayed by the absorption of strain energy due to deformation of the adhesive layer. In contrast, for MAM, peeling progressed linearly from the edge to the center of the probe. The greater flexibility of the soft block chain in the diblock copolymer resulted in improved interfacial adhesion. 1H pulse nuclear magnetic resonance analysis showed that the addition of the tackifier improved the cohesive strength of the adhesive. Adhesion strength is affected by two factors: the development of interfacial adhesion and cohesive strength. In the MAM/MA/tackifier system, the presence of MA and the tackifier improved the interfacial adhesion and cohesive strength, respectively. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013